ÍNDICE DE MEMBRANAS DEGRADADAS COMO UM TESTE DE VIGOR EM SEMENTES DE SOJA - SILVA, Kelly Gabriela Pereira; OLIVEIRA, Carlos Eduardo da Silva; SOBRINHO, Renato Lustosa; SILVA, Mennes Vieira; ZOZ, Tiago (ANAIS DO ENIC, 2020)
-